The state of knowledge of people up to 40 years of age on risk factors and prevention of colorectal cancer - Belcarz, Maria (Journal of Education, Health and Sport, 2023)
Introduction: Colorectal cancer (CRC) is the third most common malignant tumor in men and the second in women. This disease is a significant civilization and social problem. So far, the highest incidence has been among people over 60 years of age. However, nowadays, more and more cases of colorectal cancer are recorded in patients under 40 years of age. This is a very worrying phenomenon and a public health challenge. The aim : of the study was to asses the knowledge of people aged 18 to 40 on risk factors and prevention of colorectal cancer Material and method The research was conducted from November 2022 to January 2023. The research used the diagnostic survey method, while the research tool was a proprietary questionnaire. The online questionnaire concerned issues related to risk factors and prevention of colorectal cancer. The study was conducted among 185 people under 40 years of age. Results: The vast majority of respondents had heard of CRC (88.7%). According to 68.1% of respondents, the risk of CRC increases with age. Only 42.2% of the respondents were aware that colorectal cancer can develop in young people. The main predisposing factors were the presence of adenoma-type polyps in the large intestine (95.1%), excessive body weight (83.8%), incorrect diet (92.4%). Only 31.9% of the respondents correctly indicated the definition of primary prevention. Conclusions Knowledge about colorectal cancer prevention was unsatisfactory Full knowledge about preventive examinations can reduce barriers to screening. Nationwide public health efforts are needed to raise awareness of colorectal cancer among young people.